2020
DOI: 10.1038/s41598-020-65335-z
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula ventilation therapy for obstructive sleep apnea in ischemic stroke patients requiring nasogastric tube feeding: a preliminary study

Abstract: Obstructive sleep apnea (OSA) is associated with increasing risk of recurrent stroke and mortality. Nasogastric tubes used by dysphagic stroke patients may interfere with nasal continuous positive airway pressure (CPAP) due to air leakage. This study was evaluated the effects and short-term tolerability of high-flow nasal cannula (HFNC) therapy for OSA in stroke patients with nasogastric intubation. The HFNC titration study was performed in post-acute ischemic stroke patients with nasogastric intubation and OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Finally, tolerability of NHF was potentially hampered by the fact that patients were confronted with this kind of ventilatory support for the first time. At the same time, low tolerability of NHF50 in particular is in line with one recent previous report on this in adult patients with obstructive sleep apnoea [ 44 ]. In contrast, all patients had started NIV substantially earlier including the opportunity to get used to it.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, tolerability of NHF was potentially hampered by the fact that patients were confronted with this kind of ventilatory support for the first time. At the same time, low tolerability of NHF50 in particular is in line with one recent previous report on this in adult patients with obstructive sleep apnoea [ 44 ]. In contrast, all patients had started NIV substantially earlier including the opportunity to get used to it.…”
Section: Discussionsupporting
confidence: 89%
“…In twenty-nine percent of the time, the patients received an oxygen flow close to the suggested rate within 5 L/min while forty-four percent of the time, the difference between the administered and suggested oxygen flow rates are within 10 L/min. Since the high‐flow nasal oxygen (HFNO) therapy often increases flow rate in increments of 10 L/min up to 60 L/min [ 28 ], it suggests that RL-oxygen is consistent with physicians about 40–50% of the time.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study on NHF on patients with overlap syndrome. Only few studies have previously explored the effect of nasal high-flow insufflation on upper airway obstruction [13,14,19,20]. In 2007, an early physiological study showed that in 11 patients with mild to moderate OSA a transnasal airflow of 20 L/min improved the AHI, which changed from average 28 to 10, and reduced the number of arousals/hour from 18 to 8, thus improving sleep quality [13].…”
Section: Discussionmentioning
confidence: 99%